2009
DOI: 10.1097/coc.0b013e318173a563
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction After Radiotherapy for Prostate Cancer

Abstract: Erectile Dysfunction (ED) is a relatively common complication after radiotherapy for prostate cancer. The etiology of ED is unclear. It is likely related to age, pretreatment erectile function, androgen deprivation therapy, and the volume of tissue irradiated. It is unclear whether the dose to various parts of the penis, such as the penile bulb and corpora cavernosa, is related to the development of ED. Following radiotherapy, the early use of phosphodiesterase inhibitors probably reduces the risk of ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…In addition, studies using RT animal models have shown that radiation caused a reduction of nNOS-containing erectile nerves [4,5] and fibrosis of penile arteries [5,6]. Thus, similar to radical prostatectomy (RP), RT may cause ED via the destruction of cavernous nerves (CNs) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies using RT animal models have shown that radiation caused a reduction of nNOS-containing erectile nerves [4,5] and fibrosis of penile arteries [5,6]. Thus, similar to radical prostatectomy (RP), RT may cause ED via the destruction of cavernous nerves (CNs) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Die Ätiologie der postradiogenen ED ist jedoch trotz zahlreicher Studien zu verschiedenen Risikofaktoren im Rahmen der Strahlentherapie noch nicht vollständig verstanden. Neben dem Alter der Patienten, der erektilen Funktion vor Strahlentherapie, einer begleitenden antiandrogenen Therapie und dem bestrahlten Volumen, belegen einige Studien auch die Bedeutung der Strahlendosis des Bulbus penis, der Corpora cavernosa (Crura), der neurovaskulären Bündel und der A. pudenda [5,6]. Aber auch die neueren Bestrahlungsmodalitäten mit Aussparung der Gefäßregion oder die IMRT (Intensitäts-modulierte Radiotherapie) können keinen kompletten Erhalt der erektilen Funktion garantieren [7].…”
Section: Materials Und Methodenunclassified
“…The causes and exact classification of RI-ED are unknown, although cavernosal (abnormal cavernosal distensibility), arteriogenic (low peak penile blood flow rates), and neurogenic (poor response to prostaglandin injections and histologic evidence of injury) dysfunction have all been associated with RI-ED (7)(8)(9)(10). Irradiation of the bulbus penis, the posterolateral neurovascular bundles (which are composed of the venous plexus of Santorini, which drains the penis; branches of the internal pudendal artery that supply the prostate and penis; and the nerves originating from the pelvic plexus, which provide parasympathetic and sympathetic fibers to the prostate, urethra, seminal vesicles, and penile corpora cavernosa), the pudendal nerves, or some combination of these have been inconsistently implicated in RI-ED (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 98%